2021
DOI: 10.1016/j.jbc.2021.101416
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into substrate recognition and catalysis by phthalate dioxygenase from Comamonas testosteroni

Abstract: Phthalate, a plasticizer, endocrine disruptor, and potential carcinogen, is degraded by a variety of bacteria. This degradation is initiated by phthalate dioxygenase (PDO), a Rieske oxygenase (RO) that catalyzes the dihydroxylation of phthalate to a dihydrodiol. PDO has long served as a model for understanding ROs despite a lack of structural data. Here we purified PDO KF1 from Comamonas testosteroni KF1 and found that it had an apparent k … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…It is possible that iso -PDO and ortho -PDOs from related strains have similar architecture. The strain E6 iso- / ortho -PDO α-subunits share 32% identity with one another, forming a separate lineage from the α-subunits of TPADO and other α 3 β 3 -ROs with which they share ≤19% identity ( 56 ). Accordingly, the α-subunits of TPADO and a recently reported ortho -PDO structure superimpose poorly ( C. testosteroni KF1 PDO) ( SI Appendix , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that iso -PDO and ortho -PDOs from related strains have similar architecture. The strain E6 iso- / ortho -PDO α-subunits share 32% identity with one another, forming a separate lineage from the α-subunits of TPADO and other α 3 β 3 -ROs with which they share ≤19% identity ( 56 ). Accordingly, the α-subunits of TPADO and a recently reported ortho -PDO structure superimpose poorly ( C. testosteroni KF1 PDO) ( SI Appendix , Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Based upon approximately 20 unique crystal structures, it has been revealed that Rieske oxygenases assemble into heterohexameric (α 3 β 3 ) [ 21 30 ], homohexameric (α 3 α 3 ) [ 31 , 32 ], and homotrimeric (α 3 ) [ 33 40 ] architectures ( Figure 2a – c ). Some reports have also suggested that the Rieske oxygenases chlorophyll(ide) a oxygenase and phthalate dioxygenase (PDO) from Micromonas pusilla and Pseudomonas cepacia, respectively, adopt alternative dimeric and tetrameric quaternary structures [ 32 , 41 , 42 ]. However, more recent structural and biochemical data suggest that these systems instead fold into one of the above-noted traditional assemblies [ 32 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have also suggested that the Rieske oxygenases chlorophyll(ide) a oxygenase and phthalate dioxygenase (PDO) from Micromonas pusilla and Pseudomonas cepacia, respectively, adopt alternative dimeric and tetrameric quaternary structures [ 32 , 41 , 42 ]. However, more recent structural and biochemical data suggest that these systems instead fold into one of the above-noted traditional assemblies [ 32 , 41 , 42 ]. In the α 3 β 3 , α 3 α 3 , and α 3 structures, three α subunits, which each contain both metallocenters, arrange into a trimeric architecture that places Rieske cluster and iron site within electron transfer distance of one another across a subunit–subunit interface ( Figure 2a – c ).…”
Section: Introductionmentioning
confidence: 99%
“…PAH degradation by bacteria proceeds through dioxygenase attacks on a PAH to form a cis-dihydrodiol aromatic compound using two atoms of O 2 (Figure 1) [16,17] These proteins are also able to perform oxidation with a high degree of stereo-, regio-, and enantiospecificity at the catalytic mononuclear iron site [18]. Dioxygenases are metalloenzymes present in a wide variety of microorganisms that are able to oxidize PAHs using oxygen molecules and two electrons from a reductase to give cis-arene diols (Figure 1) [19,20]. A wide range of 3D dioxygenase structures have been determined, giving insight into substrate recognition and regioselectivity [19,21].…”
Section: Introductionmentioning
confidence: 99%